Pengelolaan Model Pendidikan Integratif Dalam Pencapaian Tujuan Pendidikan Nasional: Studi Kasus di Pesantren Darul Muttaqien Parung-Bogor dan Pesantren Al-Karimiyah Sawangan Baru Depok Jawa Barat - Haris, Iis Abdul; Saefuddin, Didin; Suryadi, Bambang (Ta’dibuna: Jurnal Pendidikan Islam, 2015)
Initially, pesantren is a simple religious boarding school, without systematic teaching. Nowdays, pesantren developed in such a way, either in the form of physical and system curriculum concepts. Its existence equip madrasah or college classical format. Restore the function and role of schools in national education.Reveal the purpose of this research is the management concept of the ideal model of integrative education and Viewing the relationship between management education models integrated with the achievement of the National Education held at Darul Muttaqien boarding school and Al-Karimiyah, West Java. This study used a qualitative approach to the design multicase. The technique of collecting data through interviews, participant observation and documentation. The results of this study indicate that integrative education conducted in schools that promote a very significant aspect of morality. Style education schools that emphasize a balance between science and morality will make an intelligence generation, virtuous and moral. Integrative Islamic Education seeks combines two things that is still treated dichotomacally, namely to harmonize the relationship revelation re-sense, which is dichotomacally treatment of both has resulted in the separation of religious knowledge with general knowledge. Management education in Darul Muttaqien and Al Karimiyah Muttaqien still maintaining the purity of its original identity as a place steeped in religious sciences (tafaqquh fiddin) through the classics (yellow book) written by the scholars’ medieval. However, in both educational boarding school is not just focused on the classics (read: religious knowledge), but also include general subjects and skills. Both peantren in general have responded positively to the national education goals. Keywords— education concept, education objectives, Islamic education, character education, character, akhlaq, values, morality